Arterial Stiffness and Cardiometabolic-Based Chronic Disease: The Kardiovize Study - Pavlovska, Iuliia; Mechanick, Jeffrey I; Maranhao Neto, Geraldo A; Infante-Garcia, Maria M; Nieto-Martinez, Ramfis; Kunzova, Sarka; Polcrova, Anna; Vysoky, Robert; Medina-Inojosa, Jose R; Lopez-Jimenez, Francisco; Stokin, Gorazd B; González-Rivas, Juan P (Endocrine practice, 2021)
OBJECTIVE: Arterial stiffness (ArSt) describes a loss of arterial wall elasticity and is an independent predictor of cardiovascular events. A cardiometabolic-based chronic disease model integrates concepts of adiposity-based chronic disease (ABCD), dysglycemia-based chronic disease (DBCD), and cardiovascular disease. We assessed if ABCD and DBCD models detect more people with high ArSt compared with traditional adiposity and dysglycemia classifiers using the cardio-ankle vascular index (CAVI). METHODS: We evaluated 2070 subjects aged 25 to 64 years from a random population-based sample. Those with type 1 diabetes were excluded. ABCD and DBCD were defined, and ArSt risk was stratified based on the American Association of Clinical Endocrinologists criteria. RESULTS: The highest prevalence of a high CAVI was in stage 2 ABCD (18.5%) and stage 4 DBCD (31.8%), and the lowest prevalence was in stage 0 ABCD (2.2%). In univariate analysis, stage 2 ABCD and all DBCD stages increased the risk of having a high CAVI compared with traditional classifiers. After adjusting for age and gender, only an inverse association between obesity (body mass index ≥30 kg/m2) and CAVI remained significant. Nevertheless, body mass index was responsible for only 0.3% of CAVI variability. CONCLUSION: The ABCD and DBCD models showed better performance than traditional classifiers to detect subjects with ArSt; however, the variables were not independently associated with age and gender, which might be explained by the complexity and multifactoriality of the relationship of CAVI with the ABCD and DBCD models, mediated by insulin resistance.
Keywords: diabetes; obesity; type 2 diabetes; Risk Factors; chronická nemoc; adiposity; cardio-ankle vascular index; Chronic Disease; tuhost cévní stěny; Vascular Stiffness; Ankle Brachial Index; kardiovaskulární nemoci; lidé; endokrinologové; Humans; Body Mass Index; rizikové faktory; index tělesné hmotnosti; Cardiovascular Diseases; Endocrinologists; tlakový index kotník-paže; atherosclerosis